PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK TEMA 8 SUBTEMA 3 USAHA PELESTARIAN LINGKUNGAN PEMBELAJARAN 1 - Dian Febiyani; Elly Sukmanasa; Nita Karmila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the development of e-modules based on flipbook theme 8 subtheme 3 efforts to preserve the learning environment 1 in class V SDN Cilangkap 3 Depok City and to determine the feasibility of flipbook-based e-modules for the learning process. This research has conducted validation tests on several experts in the media, language, and material fields to develop and perfect e-module products using flipbooks for students. The results of the data from the validation of media experts are 100%, which means that the e-module is very feasible to try out. Language experts obtained 100% results, which means they were declared very feasible and the results from material experts were 100% which were stated to be very feasible for testing. And based on trials that have been carried out on fifth grade students as many as 34 students obtained a proper score for use in the learning process of 97% and trials that have been carried out on teachers of 98% which means that the E-Module product using this flipbook is very feasible for used in the learning process